Analysis of factors influencing HPV vaccination intention among Chinese college students: structural equation modeling based on health belief theory - Song, Shi-Yuan; Guo, Ying; Li, Yi-Hua; Wang, Zheng; Gao, Wei (Frontiers in Public Health, 2025)
BackgroundIncreasing human papillomavirus (HPV) vaccination rates is vital for achieving society-wide public health goals, yet current research on HPV vaccine-related knowledge, vaccination intentions, and behaviors among college students in ethnic minority regions is inadequate. This investigation sought to explore the present circumstances of college students in China’s ethnic minority regions concerning their awareness, attitudes, and practices related to the HPV vaccine. This study also aimed to provide a scientific basis for future health education and HPV vaccine promotion in China’s college student population.MethodsBased on health belief theory, 1,388 valid questionnaires were collected online to investigate college students’ knowledge, beliefs, and behaviors related to HPV vaccination and the factors influencing their willingness to be vaccinated. The data were analyzed via SPSS 26.0 for descriptive analysis and Amos 24.0 for structural equation modeling, factor analysis and path analysis.ResultsThe overall HPV vaccine awareness rate was 77.9%. In terms of health attitudes, the positive intention rate was 50.4%, with females having more positive attitudes than males (OR = 2.242, 95% CI = 1.777–2.829). In terms of health behaviors, the rate of positive behaviors was low (40.0%), and the probability of positive behaviors was significantly lower for students with nonmedical-related majors than for those with medical majors (OR = 0.579, 95% CI = 0.442–0.759). The results of the structural equation modeling analysis revealed that college students’ perceptions of the perceived benefits of the HPV vaccine positively and directly affect their willingness to be vaccinated (β = 0.290, p < 0.001), and perceived severity has an indirect effect on their willingness to be vaccinated (β = 0.198, p < 0.05).ConclusionAlthough college students in ethnic minority areas have a high rate of HPV-related knowledge, their willingness to be actively vaccinated and their positive behaviors need to be improved. In addition, enhancing the levels of perceived severity and perceived efficacy among college students can help increase their willingness to receive the HPV vaccine.